Implementasi Manajemen Tenaga Kependidikan untuk Meningkatkan Kualitas Layanan Pendidikan Agama Islam di SMKS Muhammadiyah Ambarawa - Ananda, Rizki Dwi; An An Andari; Toha Ma’arif (UNISAN JURNAL, 2025)
This study aims to describe the implementation of educational staff resource management in improving the quality of Islamic Religious Education (IRE) services at SMKS Muhammadiyah Ambarawa, Pringsewu Regency, for the 2024/2025 academic year. The quality of educational services, particularly in IRE, is strongly influenced by the school’s managerial capacity in managing educational staff professionally, effectively, and with a focus on quality. Proper management of educational staff helps create a conducive work environment, efficient and accurate administrative services, and optimal support for IRE teaching and learning processes. This research employed a qualitative descriptive approach, with the subjects consisting of the school principal, IRE teachers, educational staff, and students. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman interactive model, which includes three stages: data reduction, data display, and conclusion drawing. The results showed that the implementation of educational staff resource management at SMKS Muhammadiyah Ambarawa was carried out through several strategic stages: (1) Planning of staff needs based on workload analysis and school requirements; (2) Recruitment and selection of educational staff oriented toward professional competence and Islamic values; (3) Training and professional development through administrative education workshops, digital service training, and strengthening Islamic work ethics; and (4) Performance evaluation conducted periodically to improve service effectiveness. These efforts have positively impacted work discipline, administrative efficiency, and the establishment of a productive and religious work environment. Supporting factors for the successful implementation of educational staff management include visionary leadership from the principal, strong teamwork, and an organizational culture grounded in Islamic values. Meanwhile, the challenges encountered include limited technological facilities, heavy workloads, and the need for further competency development among some staff members. The study concludes that well-planned, structured, and Islam-based management of educational staff resources is key to improving the quality of Islamic Religious Education services at SMKS Muhammadiyah Ambarawa. The findings of this research are expected to serve as a reference for other Islamic educational institutions in optimizing the role of educational staff to achieve excellent and character-based educational services.